Effect of Theobroma cocoa Extract on Olanzapine-Induced Metabolic Syndrome in Rats - Patole, Varsha; Bhawar, Sanjay; Dighe, Santosh; Ghogare, Rajashree; Sonawane, Manisha (Indian Journal of Pharmaceutical Education and Research, 2026)
Objectives: This study examined the effects of Theobroma cocoa hydro-alcoholic Extract (TCE) on the metabolic syndrome that rats developed because of olanzapine. Materials and Methods: Dry cocoa powder was macerated in 80% ethanol for seven days to create the TCE. Filtration and concentration were then carried out under lower pressure. Rats (n=6) were divided into five groups. Three dosages of TCE (100, 200, and 400 mg/kg) were administered orally for 21 days along with olanzapine (2 mg/kg/day, intraperitoneally). Body weight was measured every three days, and food intake was recorded every day. An Oral Glucose Tolerance Test (OGTT) was conducted last week. The lipid profiles that were assessed on the final day included Triglycerides (TG), Total Cholesterol (TC), HDL, LDL, and VLDL levels. The oxidative stress indicators Glutathione (GSH), Catalase (CAT), Superoxide Dismutase (SOD), and Malondialdehyde (MDA) were measured in liver tissue. Results: While olanzapine dosing decreased GSH, SOD, and HDL levels in the liver, it markedly increased weight gain, food consumption, TG, LDL, TC, VLDL, and MDA. The weight of adipose and hepatic tissue was also increased, while locomotor activity was decreased. Treatment with TCE at different doses significantly decreased food intake, TG, LDL, TC, VLDL, MDA, and weight gain. In addition, TCE decreased liver and adipose tissue weight, increased locomotor activity, and improved GSH, SOD, and HDL levels in comparison to the olanzapine group. According to these results, TCE reduces the oxidative and metabolic stress brought on by olanzapine. Conclusion: According to the study, olanzapine-induced weight gain, oxidative stress, abnormalities in lipid metabolism, and decreased locomotor activity are all mitigated by Theobroma cocoa extract.
Keywords: Olanzepine; Locomotor activity; Lipid metabolism; Weight gain; Theobroma cocoa.